2019
DOI: 10.4103/ejb.ejb_73_19
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of the diaphragm

Abstract: Background Ultrasonography is a promising technique for structural and functional evaluation of the diaphragm. It is accurate, reproducible, and portable with no ionizing radiation. Multiple studies have reported ultrasonography as the modality of choice for evaluation of the diaphragm. Objective The aim was to assess the role of ultrasound (US) in the evaluation of the diaphragm, either normal or abnormal, through evaluating its morphology, integrity, and measuring different parameters such as diaphragmatic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Among the 41 patients, 37 patients were successfully extubated with DE>1 cm.Hence we concluded that DE>1 cm could be considered for extubation. In the study conducted by Sabri et al [12], excursions in normal breathing ranged from 0.9 to 3.6 cm, with a mean of 2 cm; the mean excursion for the right hemidiaphragm was 1.85 cm; These values were also similar to the values obtained in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Among the 41 patients, 37 patients were successfully extubated with DE>1 cm.Hence we concluded that DE>1 cm could be considered for extubation. In the study conducted by Sabri et al [12], excursions in normal breathing ranged from 0.9 to 3.6 cm, with a mean of 2 cm; the mean excursion for the right hemidiaphragm was 1.85 cm; These values were also similar to the values obtained in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Common clinical features of pulmonary tuberculosis include productive cough of more than 3 weeks, weight loss, hemoptysis, night sweats, and prolonged low-grade fever (5). The diagnostic imaging modalities useful in their assessment are abdominal/ chest ultrasound, plain chest radiograph, Computerized tomography, and Magnetic Resonant Imaging (6,7).…”
mentioning
confidence: 99%